Geração e qualidade de resíduos sólidos domiciliares de diferentes estratos sociais na cidade de Aracaju-SE - Nascimento, Priscilla de Andrade (2012)
Currently, issues related to municipal solid waste are a great concern to society, they experience environmental problems and public health. The predominant solid waste in urban areas have a higher degree of complexity because it involves components such as plastic, paper, glass, aluminum, ferrous metals, etc. These, in turn, if not reused or recycled, can impact the environment. At the principle, the waste was generated in smaller amounts being made entirely of organic substance, this was easily assimilated by nature, but as the companies were growing and developing the amount of waste has increased considerably, with it becoming a problem of global scale. Changes in lifestyle of the population associated with per capita income, particularly in classes with higher purchasing power, as society has led to unsustainable as daily products are consumed and discarded immediately from different places generating garbage. Waste recycled add a market value besides has a low degree of environmental damage, however, in most Brazilian cities, particularly in State of Sergipe, the waste produced in homes have as their final destination landfills. The waste when disposed of improperly and without treatment may cause risks to people through contaminated water, soil and atmosphere and attract vectors that transmit various diseases. This research intends to identify by physical characterization and gravimetric composition (percentage by weight of each component), waste generated in households of three specific neighborhoods in Aracaju namely: Salgado Filho, Cirurgia and Porto Dantas, among which are socioeconomic and different environmental qualities. By the characterization of solid waste, we determined that the neighborhood Salgado Filho generated more organic substance than other neighborhoods in the search. Long-life Packaging was found more frequently in neighborhoods Salgado Filho and Cirurgia, these are considered upper class and middle respectively, however, the discard of such material has not been found in Porto Dantas, as well as other types of materials potentially recyclable. The research conclusions indicates that the Aracaju city waste is disposed in the landfill of neighborhood Santa Maria, without any monitoring or oversight, causing the worsening of environmental problems.